Karyotype inconsistencies in the taxonomy of the genus Oxalis (Oxalidaceae) - Moura, Amália Ibiapino; Oliveira, Ykaro Richard; da Silva, Paulo Henrique; Mata-Sucre, Yennifer; de Carvalho, Reginaldo; de Sales, Margareth Ferreira; de Abreu, Maria Carolina (Iheringia, Série Botânica., 2020)
The family Oxalidaceae consists of six genera, of which Oxalis is the most representative. This genus is subdivided into four subgenera, and its species present great morphological variation, which makes it difficult to identify them. The aim of this study was to make a survey of scientific publications which presented chromosome numbers of species of Oxalis, and to compare the chromosome numbers to the taxonomic classification proposed by Alicia Lourteig. Published chromosome counts were found for 112 species. We infered that there is apparently no relation between the chromosome numbers of the species of Oxalis and the taxonomic classification proposed by Lourteig, as species belonging to a same subgenus did not present a coherent pattern in chromosome numbers.